Compact Wideband Circularly Polarized Antenna with Symmetric Parasitic Rectangular Patches for Ka-Band Applications - Rongling Jian; Yueyun Chen; Taohua Chen (International Journal of Antennas and Propagation)
In this paper, a novel wideband circularly polarized (CP) millimeter wave (mmWave) microstrip antenna is presented. The proposed antenna consists of a central patch and a microstrip line radiator. The CP radiation is achieved by loading a rectangular slot on the ground plane. To improve the 3-dB axial ratio bandwidth (ARBW), two symmetric parasitic rectangular patches paralleled to a central patch and a slit positioned to the right of the central patch are loaded. To verify this design, the proposed antenna is fabricated with a small antenna of 2.88 × 3.32 × 0.508 mm3. The measured impedance bandwidth (IMBW) for S11<−10 dB of the proposed antenna is 35.97% (22.8 to 33.8 GHz). Meanwhile, the simulation result shows that the 3-dB ARBW is 15.19% (28.77 to 33.5 GHz) within impedance bandwidth, and the peak gain is from 5.08 to 5.22 dBic within 3-dB ARBW. The proposed antenna is suitable for CP applications in the Ka-band.